Genetic rodent models of brain disorders: Perspectives on experimental approaches and therapeutic strategies. Issue 3 (14th September 2017) - McGraw, Christopher M.; Ward, Christopher S.; Samaco, Rodney C.
Abstract : Neurobehavioral disorders comprised of neurodegenerative, neurodevelopmental, and psychiatric disorders together represent leading causes of morbidity and mortality. Despite significant academic research and industry efforts to elucidate the disease mechanisms operative in these disorders and to develop mechanism‐based therapies, our understanding remains incomplete and our access to tractable therapeutic interventions severely limited. The magnitude of these short‐comings can be measured by the growing list of disappointing clinical trials based on initially promising compounds identified in genetic animal models. This review and commentary will explore why this may be so, focusing on the central role that genetic models of neurobehavioral disorders have come to occupy in current efforts to identify disease mechanisms and therapies. In particular, we will highlight the unique pitfalls and challenges that have hampered success in these models as compared to genetic models of non‐neurological diseases as well as to symptom‐based models of the early 20th century that led to the discovery of all major classes of psychoactive pharmaceutical compounds still used today. Using examples from specific genetic rodent models of human neurobehavioral disorders, we will highlight issues of reproducibility, construct validity, and translational relevance in the hopes that these examples will be instructive toward greater success in future endeavors. Lastly, we will champion a two‐pronged approach toward identifying novel therapies for neurobehavioral disorders that makes greater use of the historically more successful symptom‐based approaches in addition to more mechanism‐based approaches.